Identity and industry : making media multicultural in Canada - Hayward, Mark, 1975- (McGill-Queen's University Press, 2019)
"In 1947, grocer Johnny Lombardi went on air for the first time to share the sounds of "sunny Italy" with the radio listeners of Toronto. Meanwhile, in cities across the country, a handful of theatres began to show films in foreign languages. In the decade after the Second World War, these events were some of the earliest indications of the nationwide changes taking place in Canadian media as it responded to the new cultural, political, and economic visibility of cultural and linguistic minorities. Identity and Industry explores how ethnocultural media in Canada developed between the end of the Second World War and the arrival of digital media. Through chapters dedicated to film exhibition, newspapers, radio, and television, Mark Hayward documents the industrial and institutional frameworks that defined the role of media in Canadian multiculturalism. Drawing on extensive archival research, the book situates late twentieth-century "ethnic" media at the intersection of demand, cultural integration, and the changing economics of popular culture. As the development of ethnocultural media continues to shape Canadian society in the age of digital media, Identity and Industry provides richly detailed historical context for contemporary debates about identity and culture."--